PENGUATAN MATERI KEWIRAUSAHAAN DI ERA PELAJAR PANCASILA BAGI SISWA SMA NEGERI 14 SAMARINDA - Siti Akmalia; Milawati Milawati; Tri Widyasari; Noredyo Molyaningrum (Jurnal Abdi Insani, 2023)
A student is a generation that will play an important role in the economy because students are a generation of social revolutionaries who have enthusiasm, ability, competitiveness, strong mental and physical abilities and are responsive so that there is an entrepreneurial theme. The aim of this activity is to increase the entrepreneurial spirit of students, namely by increasing knowledge about entrepreneurship. The method used in this strengthening is by using a lecture method which is carried out by providing an explanation about strengthening entrepreneurship material, then continuing in the form of games and a question and answer process. The results of the activities in this activity are the transfer of knowledge about entrepreneurship material which will be conveyed in the workshop activities, it is hoped that there will be an increase in students' understanding of strengthening entrepreneurship and encouraging students to think more actively, creatively and innovatively and have an entrepreneurial spirit, especially to complete assignments. in the Strengthening Pancasila Student Profile (P5) Project activities. With this activity, strengthening entrepreneurship material can be used as a reference for students to increase their knowledge to carry out entrepreneurial activities.